Um Teorema de Ponto Fixo e Aplicações a Equações Elípticas Semilineares - Marques, Dayvid Geverson Lopes (2012)
In this work, we study a fixed point theorem for increasing operators in ordered normed spaces and we apply it in order to obtain results of existence of weak solution for semilinear elliptic equations of type 8<: ---u = f(x; u) + h; in u = 0; on @ ; where - RN is a smooth domain, f : -R --! R satisfies some convenient conditions and h 2 H--1(.